Exploring the association between serum phosphate levels and mortality in patients hospitalized with infectious diseases: a nationwide study - Frenkel, Amit; Shiloh, Adi; Vinokur, Victoria; Boyko, Matthew; Binyamin, Yair; Dreiher, Jacob (Frontiers in Medicine, 2024)
Objective The purpose of this study was to examine associations of serum phosphate levels with mortality, target organ damage and length of hospital stay in adults with infectious diseases hospitalized outside of the intensive care unit. Methods This nationwide retrospective cohort study comprised patients admitted with infections, to medical and surgical departments in eight tertiary hospitals during 2001–2020. The main exposure variable was the first serum phosphate levels at admission (up to 1 week). The analysis included multivariable logistic regression models and quantile regression. Results Of 126,088 patients (49% males, mean age: 69.3 years), 24,809 (19.7%) had decreased phosphate levels, 92,730 (73.5%) normal phosphate levels, and 8,549 (6.8%) elevated phosphate levels on admission. Overall- and in-hospital mortality rates were highest among those with hyperphosphatemia (74.5 and 16.4%, respectively), followed by those with normophosphatemia (57.0 and 6.6%), and lastly the hypophosphatemia group (48.7 and 5.6%); p < 0.001 for all. After adjusting for confounders, the lowest predicted mortality rate was observed in the normophosphatemia group. In the multivariable model, hyperphosphatemia conferred a higher probability of target organ damage (OR [95% CI]: 2.43 [2.06–2.86]), while moderate hypophosphatemia conferred a lower probability (OR [95% CI]: 0.73 [0.65–0.82]), compared to normal phosphate levels and extreme hypophosphatemia showed a non-significant association (OR [95% CI]: 0.87 [0.57–1.28]). The associations were independent of renal failure. In a multivariable model, hyperphosphatemia was associated with a slight increase of 0.33 days in length of stay compared to normal phosphate levels. Conclusion A J-shaped relation was found between phosphate levels and prognosis in patients hospitalized with infectious diseases, regardless of their renal function.